[Patching up ; Minsa'y isang gamu-gamo ; Black theatre [videorecording] - Lazaro, Cheche (The Probe Team, 1991)
Deals with the services given by two doctors which resulted to the death of the patients; Followers which are known only to the club they belong and to the idol they have sworn and dying loyalty to; Puppet show as an alternative way of teaching children.